How do energy consumption, output, energy price, and population growth correlate with CO2 emissions in Liberia?. (30th September 2019) - Gbatu, Abimelech Paye; Wang, Zhen; Wesseh, Presley K.; Sesay, Vamuyan A.
Researches that provide insights on major environmental matters are necessary for policy decision making in Liberia. Therefore, we employ autoregressive distributed lag (ARDL) model to gauge short-and-long-run associations between CO2 emissions and Liberia's key macroeconomic variables. The ARDL long-run outcomes are compared against results from dynamic ordinary least square (DOLS) approach. The short-run outcomes reveal that energy consumption (EC) and real output (GDP) have significant positive impacts on CO2 emissions in Liberia. In the long-run, both ARDL and DOLS estimates show significant positive impacts of EC, real GDP and oil price on CO2 emissions. Hence, we find the existence of the environmental Kuznets curve (EKC) hypothesis for Liberia. Therefore, we argue that EC is the main factor that promotes economic growth in Liberia, but growth in EC and real GDP stimulate CO2 emissions growth. Thus, new carbon free technologies that reduce dependence on primary energy use are required.